2016
DOI: 10.1111/sifp.12005
|View full text |Cite
|
Sign up to set email alerts
|

How User Fees Influence Contraception in Low and Middle Income Countries: A Systematic Review

Abstract: Accessible and quality reproductive health services are critical for low‐ and middle‐income countries (LMICs). After a decade of waning investment in family planning, interest and funding are growing once again. This article assesses whether introducing, removing, or changing user fees for contraception has an effect on contraceptive use. We conducted a search of 14 international databases. We included randomized controlled trials, interrupted‐time series analyses, controlled before‐and‐after study designs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…The major strands of evidence on factors that influence method choice fall into the following categories: information, availability, access, and affordability (Tsui and Ochoa 1992; Korachais et al. 2016); counseling, client provider interactions, and provider bias, including studies in Kenya (Kim et al. 1998); sociodemographic correlates of method‐choice, again including studies in Kenya and neighboring Tanzania (Magadi and Curtis 2003; Chen and Guilkey 2003); desired attributes of methods and acceptability (Snow et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major strands of evidence on factors that influence method choice fall into the following categories: information, availability, access, and affordability (Tsui and Ochoa 1992; Korachais et al. 2016); counseling, client provider interactions, and provider bias, including studies in Kenya (Kim et al. 1998); sociodemographic correlates of method‐choice, again including studies in Kenya and neighboring Tanzania (Magadi and Curtis 2003; Chen and Guilkey 2003); desired attributes of methods and acceptability (Snow et al.…”
Section: Introductionmentioning
confidence: 99%
“…O ver the past half century, a huge literature on contraceptive method choice has been generated including several edited volumes (Russell et al 2000;Bulatao et al 1989;Sundari Ravindran et al 1997) and reviews (Daniele et al 2017;Williamson et al 2009;Wyatt et al 2014). The major strands of evidence on factors that influence method choice fall into the following categories: information, availability, access, and affordability (Tsui and Ochoa 1992;Korachais et al 2016); counseling, client provider interactions, and provider bias, including studies in Kenya (Kim et al 1998); sociodemographic correlates of method-choice, again including studies in Kenya and neighboring Tanzania (Magadi and Curtis 2003;Chen and Guilkey 2003); desired attributes of methods and acceptability (Snow et al 1997;Keller 1979); the behavior and views of sexual partners and members of persons' social network (Godley 2001;Kimuna and Adamchak 2001); and a very large number of publications on opinions and fears about specific methods among Kenyan women and, less commonly, among men (Kamau et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…); (iii) introducing, removing, or changing out‐of‐pocket payments or user fees (Korachais et al. ); (iv) results‐based financing (Blacklock et al. ), including all interventions involving payment for performance that have a supply‐side component; and (v) social protection programs that provided a voucher (Bellows et al.…”
Section: Methodsmentioning
confidence: 99%
“…Five intervention groups were identified, and for each a specific systematic review was carried out. The specific interventions groups were: (i) introduction of community financing and community-based health insurance (Karra et al 2016), which included interventions for family planning that focus on the role of the community in mobilizing, pooling, and allocating reproductive health resources through various health financing instruments, including micro-insurance, microfinance and microcredit, mutual health organizations, and community-managed user fees; (ii) introduction of conditional and unconditional cash transfers (Khan et al 2016); (iii) introducing, removing, or changing out-of-pocket payments or user fees (Korachais et al 2016); (iv) results-based financing (Blacklock et al 2016), including all interventions involving payment for performance that have a supply-side component; and (v) social protection programs that provided a voucher (Bellows et al 2016) subsidy to disadvantaged clients and reimbursed healthcare workers for providing contraceptive services at a pre-defined quality standard, including referral vouchers. Social marketing and franchising were not included as these were examined by other recent systematic reviews (Sweat et al 2012;Westley and Shochet 2013).…”
Section: Interventionsmentioning
confidence: 99%
“…• This has included systematic reviews of specific financing models (and their effective inclusion of FP), such as community financing and community-based health insurance (Karra et al, 2016), conditional and unconditional cash transfers (Khan et al, 2016), introducing, removing, or changing OOP or user fees (Korachais et al, 2016), results-based financing (Blacklock et al, 2016), performance-based incentives (Bellows et al, 2014), and social protection programs that provide a voucher subsidy (Bellows et al, 2016). A summary of the systematic reviews concluded that there is 'limited scientific evidence on the effectiveness of the various financing mechanisms for contraception' and that more robust studies are required (Lissner and Ali, 2016).…”
Section: Section 2 Health Financing and Family Planningmentioning
confidence: 99%